Solve for x
x = \frac{\sqrt{2549} + 7}{50} \approx 1.149752445
x=\frac{7-\sqrt{2549}}{50}\approx -0.869752445
Graph
Share
Copied to clipboard
x^{2}-0.28x+0.0196=1+0.14^{2}
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(x-0.14\right)^{2}.
x^{2}-0.28x+0.0196=1+0.0196
Calculate 0.14 to the power of 2 and get 0.0196.
x^{2}-0.28x+0.0196=1.0196
Add 1 and 0.0196 to get 1.0196.
x^{2}-0.28x+0.0196-1.0196=0
Subtract 1.0196 from both sides.
x^{2}-0.28x-1=0
Subtract 1.0196 from 0.0196 to get -1.
x=\frac{-\left(-0.28\right)±\sqrt{\left(-0.28\right)^{2}-4\left(-1\right)}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, -0.28 for b, and -1 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-0.28\right)±\sqrt{0.0784-4\left(-1\right)}}{2}
Square -0.28 by squaring both the numerator and the denominator of the fraction.
x=\frac{-\left(-0.28\right)±\sqrt{0.0784+4}}{2}
Multiply -4 times -1.
x=\frac{-\left(-0.28\right)±\sqrt{4.0784}}{2}
Add 0.0784 to 4.
x=\frac{-\left(-0.28\right)±\frac{\sqrt{2549}}{25}}{2}
Take the square root of 4.0784.
x=\frac{0.28±\frac{\sqrt{2549}}{25}}{2}
The opposite of -0.28 is 0.28.
x=\frac{\sqrt{2549}+7}{2\times 25}
Now solve the equation x=\frac{0.28±\frac{\sqrt{2549}}{25}}{2} when ± is plus. Add 0.28 to \frac{\sqrt{2549}}{25}.
x=\frac{\sqrt{2549}+7}{50}
Divide \frac{7+\sqrt{2549}}{25} by 2.
x=\frac{7-\sqrt{2549}}{2\times 25}
Now solve the equation x=\frac{0.28±\frac{\sqrt{2549}}{25}}{2} when ± is minus. Subtract \frac{\sqrt{2549}}{25} from 0.28.
x=\frac{7-\sqrt{2549}}{50}
Divide \frac{7-\sqrt{2549}}{25} by 2.
x=\frac{\sqrt{2549}+7}{50} x=\frac{7-\sqrt{2549}}{50}
The equation is now solved.
x^{2}-0.28x+0.0196=1+0.14^{2}
Use binomial theorem \left(a-b\right)^{2}=a^{2}-2ab+b^{2} to expand \left(x-0.14\right)^{2}.
x^{2}-0.28x+0.0196=1+0.0196
Calculate 0.14 to the power of 2 and get 0.0196.
x^{2}-0.28x+0.0196=1.0196
Add 1 to 0.0196.
\left(x-0.14\right)^{2}=1.0196
Factor x^{2}-0.28x+0.0196. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x-0.14\right)^{2}}=\sqrt{1.0196}
Take the square root of both sides of the equation.
x-0.14=\frac{\sqrt{2549}}{50} x-0.14=-\frac{\sqrt{2549}}{50}
Simplify.
x=\frac{\sqrt{2549}+7}{50} x=\frac{7-\sqrt{2549}}{50}
Add 0.14 to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}